Religious Factor in Nigeria External Relations - Balogun, Olaniran O. E. (NIU Journal of Social Sciences; Vol 6 No 1 (2020): KIU Journal of Social Sciences, Vol. 6 No. 1, March 2020, 2020)
Religion builds human belief system. It is a weapon that shapes one’s attitude, norms, culture and deed in life. When religion is taken to a large extent it makes its followers so submissive that scarcely can they do anything in their life times without using it lay sown principles as guide. Nigeria is a notable country in the western part of African continent which practices three dominant religions. However the imbibed/accultured religion (Christianity in the South and Islam in the North), have over powered the cultural ones (traditional religion). Religion can also be seen as an act of God fearing and of a monastic order and that belief in the existence of a supernatural ruling power the creator and controller of the universe, who has given to man a spiritual nature which continues to exist after one’s death. These religious groups play several roles in tilting the policies of Nigeria internal and external dealings as a Muslim leader prefers to work with Muslim administrators while those of Christians have faith in co-Christians irrespective of the competency and experiences of governance of the sect members. This also affects the external relationships these leaders propose or entered into while they are in power. Keywords: Religion, human; attitudinal weapon; submissive followers; Christianity, Islam and Buddahism, monastic order; Traditional